Work Flexibility, Digital Collaboration Capability, and Agile Work Autonomy and Employee Well-Being in Ibu Kota Nusantara (IKN), Indonesia: The Mediating Role of Government Support - Rizki Fajar Putranto; Budi Hermana; Sudaryanto (Global Research Collaboration, 2026)
The rapid development of digital transformation and smart-city initiatives has accelerated the adoption of New Ways of Working (NWOW), including work flexibility, digital collaboration capability, and agile work autonomy. However, evidence regarding their effects on employee well-being and the role of government support remains limited, particularly within emerging smart-city ecosystems such as Ibu Kota Nusantara (IKN), Indonesia. This study aims to examine the influence of Work Flexibility, Digital Collaboration Capability, and Agile Work Autonomy on Employee Well-Being, with Government Support serving as a mediating variable. A quantitative research approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 400 employees working across various business sectors in IKN, including MSMEs, digital startups, logistics, retail, creative industries, and professional services. The data were analyzed using SmartPLS to assess both direct and indirect relationships among the constructs. The results indicate that Digital Collaboration Capability has a significant positive effect on Employee Well-Being, whereas Work Flexibility and Agile Work Autonomy do not directly influence Employee Well-Being. All three NWOW dimensions significantly affect Government Support, which in turn exerts a strong positive effect on Employee Well-Being. Mediation analysis shows that Government Support fully mediates the relationships between Work Flexibility and Employee Well-Being and between Agile Work Autonomy and Employee Well-Being, while partially mediating the relationship between Digital Collaboration Capability and Employee Well-Being. Government Support plays a critical role in translating NWOW practices into positive employee well-being outcomes within the evolving smart-city ecosystem of IKN. The findings extend the Job Demands–Resources Theory and Social Support Theory by highlighting institutional support as a key resource in digital work environments and provide practical implications for policymakers and organizations in designing sustainable and employee-centered work systems.